Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
[tex]x^4+x^2-6=0 \\
(x^2)^2+x^2-6=0 \\ \\
a=1 \\ b=1 \\ c=-6 \\ b^2-4ac=1^2-4 \times 1 \times (-6)=1+24=25 \\ \\
x^2=\frac{-b \pm \sqrt{b^2-4ac}}{2a}=\frac{-1 \pm \sqrt{25}}{2 \times 1}=\frac{-1 \pm 5}{2} \\
x^2=\frac{-1-5}{2} \ \lor \ x^2=\frac{-1+5}{2} \\
x^2=\frac{-6}{2} \ \lor \ x^2=\frac{4}{2} \\
x^2=-3 \ \lor \ x^2=2 \\
x=\pm \sqrt{-3} \ \lor \ x=\pm \sqrt{2} \\
\boxed{x=-i\sqrt{3} \hbox{ or } x=i\sqrt{3} \hbox{ or } x=-\sqrt{2} \hbox{ or } x=\sqrt{2}}[/tex]
[tex]x^4+x^2-6=0\\
x^4+3x^2-2x^2-6=0\\
x^2(x^2+3)-2(x^2+3)=0\\
(x^2-2)(x^2+3)=0\\
x^2-2=0 \vee x^2+3=0\\
x^2=2 \vee x^2=-3\\
x=-\sqrt2 \vee x=\sqrt2 \vee x=-i\sqrt3 \vee x=i\sqrt3[/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.